(untitled) - Benson, Harold J. (Boston, 2007)
The classic resource for undergraduate microbiology laboratory courses just keeps getting better. The self-contained, clearly illustrated exercises and four-color format make Microbiological Applications: Laboratory Manual in General Microbiology the ideal lab manual. Appropriate for either a majors or non-majors lab course, this lab manual assumes no prior organic chemistry course has been taken
Vi sinh học đại cương B
Keywords: Microbiology,Vi sinh vật học; Tài liệu hướng dẫn thực hành